Transient High Strain Rate During Localized Viscous Creep in the Dry Lower Continental Crust (Lofoten, Norway) - Campbell, L. R.; Menegon, L. (Journal of Geophysical Research: Solid Earth, 2019)
Understanding the ability of the lower crust to support transient changes in stresses and strain rates during the earthquake cycle requires a detailed investigation of the deformation mechanisms and rheology of deep crustal fault rocks. Here, we show that lower crustal pseudotachylyte-bearing shear zones are able to accommodate short-term episodes of high strain rate and high stress deformation by accelerated viscous creep, followed by a reduction in stresses to some ambient deformation condition. Quartz microstructure within pseudotachylyte-bearing shear zones in otherwise undeformed granulites from Lofoten, Norway, indicates that dynamic recrystallization occurred during viscous creep under rapid strain rates and high stresses of ~10−9 s−1 and ~100 MPa, respectively. Lower stress microstructures (i.e., foam textures) are also recorded in the shear zones, indicating spatial and temporal variations of stress and strain rate during deformation cycles. Both the high and lower stress quartz recrystallization took place under granulite facies conditions of 650°C–750°C and 0.7–0.8 GPa and represented a record of highly localized viscous creep within the lower crust. This implies that lower crustal pseudotachylytes are potentially able to form extremely localized weak zones within strong lower crust, enabling a deep mechanical response to perturbations in stress and strain rate such as those experienced during the seismic cycle, for example, seismogenic loading followed by subsequent postseismic relaxation.